Evaluasi Kinerja Reksa Dana Saham Di Indonesia Menurut Metode Sharpe, Treynor dan Jensen Serta Perbandingan Return Reksa Dana Saham Dengan LQ45 Periode Januari 2009 – Juni 2010 - Ibad, Akromul; Adhidarma, Adrianus (Business and Management Review, 2012)
The purpose of this research is to measure the performance of Equtiy mutual fund by the method of Sharpe, Treynor and Jensen and compare Equity mutual fund return with return of LQ45.The theories used in this research related with the investment, risk, return, and portfolio. Equity Fund performance measurement based on the method of Sharpe, Treynor and method of Jensen's  is also one of the crucial theory base. Within the framework of thought, Equity Fund Return, LQ45 Return, Return of SBI, and the risk (standard deviation and beta ) will affect the performance of  Equity Fund. The object of this research is the Equity Fund that registered in the period January 2009 to June 2010, LQ45 index and SBI interest rate (BI Rate) period from January 2009 until June 2010. Research variable is Net Asset Value, LQ45, SBI interest rate, and return. Where SBI interest rate (BI Rate) serves as the Risk Free Return. This research uses 24 of the Equtiy Fund recorded during the period January 2009 to June 2010. Data processed by calculating the average return LQ45, the average return of Equity Fund as a whole or sub-period, the average return of SBI, and risk calculation of beta and standard deviation. Based on the results of data processing, the performance of Equity mutual fund  can be measured by the method of Sharpe, Treynor and Jensen. Then, perform the comparison of mutual fund returns with returns LQ45 Shares (which represents the market return) The final result of all the research shows the whole period, the product Panin Dana Maksima showed the best performance based on the three methods.Meanwhile, BNI Dana Berkembang as the worst performance based on these methods. In calculating the performance of the Fund Shares that will be used as investment vehicles, can use the method of Sharpe, Treynor and Jensen, so investors are keen to see the performance of Equity Mutual Fund. Key words : Equity mutual fund, method of Sharpe, Treynor, Jensen, Return of LQ45